Single-cell atlas of human penile corpus cavernosum reveals cellular and functional heterogeneity of aging-related erectile dysfunction - Zhang, Bailing; Zhao, Xueheng; Cao, Jian; Liu, Zhizhong; Wang, Xiaoyan; Li, Ran; Bo, Hao; Xu, Kongrong; Guo, Jingtao (Frontiers in Endocrinology, 2025)
BackgroundWith the acceleration of the aging process, the prevalence and severity of erectile dysfunction (ED) related to aging continue to rise, significantly impacting the physical and mental health of patients and their partners.ObjectivesThe objective of this study was to elucidate the cellular and transcriptomic heterogeneity and immune microenvironment of the aging penile corpus cavernosum in aging-related ED (ARED), while also exploring the potential pathological mechanisms driving ARED pathogenesis.Materials and methodsIn this study, we performed single-cell RNA sequencing on penile tissues from six older patients with ARED, including four older mild ED (OmED) and two older severe ED (OsED) cases, and compared with three younger healthy controls from public data.ResultsThrough clustering and comparative analysis, we identified nine major cell types including immune cells. Our research revealed the heterogeneity of smooth muscle cells (SMC), endothelial cells (EC) and immune cells in penile environment, and determined the key cell subsets, such as C1_RERGL (a subcluster of SMC) and Macro_CXCL8, and molecular features involved in the pathogenesis of ARED. Furthermore, by constructing a comprehensive cellular communication network, the signals and interactions between macrophages (Macro) and other cell types were emphasized. We found that the interaction of ligand-receptor pairs such as CXCL2/3/8 – ACKR1 and HLA-E – KLRK1 were enhanced in the ARED group.Discussion and conclusionThe mild ED phase represents a critical window of cellular functional transition in penile tissue. In ARED, we observed functional dysfunction of EC and SMC, accompanied by changed expression levels of key genes. Concurrently, the pro-inflammatory Macro_CXCL8 exhibited increased proportion in the microenvironment, which may contribute to disease progression. This work not only provides a detailed description of the cellular atlas of the aging penis but also offers new insights into its role in the pathogenesis of ARED and may provide potential targets for the development of new therapies for ARED.